Structural Convergence of Bulgaria With the Euro Area - Stefanova, Kristina (Research Papers, 2021)
The paper aims to verify the existence of structural convergence of Bulgaria with the euro area, which is an additional assessment of the readiness of the economy to adopt the euro. By evaluating the divergence index and applying sigma convergence analysis, the existence of structural convergence of Bulgaria to the Eurozone in the period 2000 – 2019 regarding the distribution of employment among economic sectors is identified. There is also convergence between Bulgaria and the euro area regarding the relative share of employment also exists in the agriculture, forestry and fisheries sector and the services sector, but divergence in the industry sector.
Keywords: Divergence index; Sigma convergence; Bulgaria; Structural convergence; Euro area; Employment